The effectiveness of contextual approach on students' comprehension ability - Ngaderi Ngaderi; Mentari Eka Wahyuni (CV. FOUNDAE, 2021)
This study aimed to determine the effectiveness of the contextual approach in improving students' algebraic arithmetic operations. This research is a Classroom Action Research (CAR) conducted in two cycles with each cycle consisting of two meetings. Data collecting techniques conducted in each cycle were tests and observation. The data analysis was performed on students' learning outcomes and the results of observations. Based on the analysis performed in the first cycle, students had poor learning outcomes in algebraic arithmetic operations. After improvements were made in the second cycle, there was an increase in the students test results. Furthermore, the observations obtained a percentage increase in student activity between the first cycle and the second cycle. This study shows that the contextual approach is quite effective in improving the understanding of the seventh-grade students in algebraic arithmetic operations.